Health service delivery and political trust in Nigeria. (April 2019) - Chukwuma, Adanna; Bossert, Thomas J.; Croke, Kevin
Abstract: Do improvements in health service delivery affect trust in political leaders in Africa? Citizens expect their government to provide social services. Intuitively, improvements in service delivery should lead to higher levels of trust in and support for political leaders. However, in contexts where inadequate services are the norm, and where political support is linked to ethnic or religious affiliation, there may be weak linkages between improvements in service delivery and changes in trust in political leaders. To examine this question empirically, we take advantage of a national intervention that improved health service delivery in 500 primary health care facilities in Nigeria, to estimate the impact of residence within 10 km of one or more of the intervention facilities on trust in the president, local councils, the ruling party, and opposition parties. Using difference-in-difference models, we show that proximity to the intervention led to increases in trust in the president and the ruling party. By contrast, we find no evidence of increased trust in the local council or opposition parties. Our study also examines the role of ethnicity and religious affiliation in mediating the observed increases in trust in the president. While there is a large literature suggesting that both the targeting of interventions, and the response of citizens to interventions is often mediated by ethnic, geographic or religious identity, by contrast, we find no evidence that the intervention was targeted at the president's ethnic group, zone, or state of origin. Moreover, there is suggestive evidence that the intervention increased trust in the president more among those who did not share these markers of identity with the president. This highlights the possibility that broad-based efforts to improve health services can increase trust in political leaders even in settings where political attitudes are often thought to be mediated by group identity. Highlights: The intervention was not targeted at the president's ethnicity or state of origin. Service improvements led to increases in trust in the president and ruling party. Trust increased among respondents outside the president's ethnicity or state of origin.